Lyapunov-Type Inequalities for a System of Nonlinear Differential Equations (Communications in Mathematical Research, 2019)
This paper presents several new Lyapunov-type inequalities for a systemof first-order nonlinear differential equations. Our results generalize and improvesome existing ones.
Keywords: Lyapunov-type inequality; nonlinear differential equation; Hamiltonian system